1995
DOI: 10.1126/science.270.5241.1485
|View full text |Cite
|
Sign up to set email alerts
|

Autoencapsulation Through Intermolecular Forces: A Synthetic Self-Assembling Spherical Complex

Abstract: The synthesis and characterization of a system for the study of molecular recognition phenomena are described. The system involves a tetraurea molecule that is capable of assembly into various associated states through hydrogen bonding. In organic solvents, the dynamic transition between a low-ordered (aggregate) state and a highly ordered dimeric assembly can be induced by the introduction of smaller molecules of appropriate size and shape. These smaller molecules, such as benzene, adamantanes, and ferrocenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
100
0
5

Year Published

1998
1998
2009
2009

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 234 publications
(105 citation statements)
references
References 17 publications
0
100
0
5
Order By: Relevance
“…USA 96 (1999)dissociation rate of 1⅐P⅐1 can be obtained from heterodimerization experiments using two different softballs. To a solution of 1⅐P⅐1 was added another softball (lacking phenolic hydroxyl groups) (17). The appearance of the new heterodimer containing P requires the dissociation of 1⅐P⅐1 and takes place over the course of days.…”
Section: Resultsmentioning
confidence: 99%
“…USA 96 (1999)dissociation rate of 1⅐P⅐1 can be obtained from heterodimerization experiments using two different softballs. To a solution of 1⅐P⅐1 was added another softball (lacking phenolic hydroxyl groups) (17). The appearance of the new heterodimer containing P requires the dissociation of 1⅐P⅐1 and takes place over the course of days.…”
Section: Resultsmentioning
confidence: 99%
“…Upon binding of a guest, for example, adamantane or ferrocene, in 20-20, two molecules of solvent that are present in the cavity are released, resulting in a favorable increase in entropy. NMR studies also revealed that the softball was capable of encapsulating two aromatic solvent molecules, 82,83 and this propensity stimulated the researchers to utilize the "softball" as a microreactor for bimolecular reactions. An example is depicted in Figure 3a, viz., the Diels-Alder reaction between p-benzoquinone 21 and cyclohexadiene 22.…”
Section: Noncovalent Systemsmentioning
confidence: 99%
“…Many investigations have been devoted to the study, the design, and the synthesis of new molecular containers. Thus, different guest molecules have been trapped in a large variety, in size and shape, of host cages [15][16][17][18][19]. Molecular container compounds have been used for different purposes such as: to inhibit very reactive species, to isolate molecules from their surrounding, as a chamber for micro-reactions, to store atoms, ions, or small molecules such as H 2 and CH 4 .…”
Section: Introductionmentioning
confidence: 99%